2001
DOI: 10.1002/hipo.1059
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of isolation‐induced hypertension by intrahippocampal administration of a nonpeptide kappa‐opioid receptor agonist

Abstract: Previous research in this laboratory showed that hypertension in the spontaneous hypertensive rat (SHR) appears to correlate to insufficient production of hippocampal dynorphins, and that blood pressure could be reduced by intrahippocampal administration of dynorphins and nonpeptide kappa agonists. The purpose of the present study was to investigate whether kappa agonists could prevent the development of hypertension in a different hypertensive model, i.e., the isolated male rat model of hypertension (IHR). Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Meta-analysis of fifteen articles (Rodgers and Cole, 1993;Haller et al, 2000;Blednov et al, 2001;Cheeta et al, 2001;Lapiz et al, 2001;Wright and Ingenito, 2001;Majercsik et al, 2003;Moragrega et al, 2003;Abramov et al, 2004;Wei et al, 2007;Koike et al, 2009;Santos et al, 2010;Cuenya et al, 2012;Lukkes et al, 2009;Hermes et al, 2011) on social isolation revealed it had a small anxiogenic effect (g = 0.37 [95CI 0.15, 0.58], p = 7.8 x 10 -4 ; Figure 6C). However, Egger's regression revealed funnel plot asymmetry, while trim-and-fill adjustment reduced the anxiogenic effect to only 0.15 g [95CI -0.10, 0.40], a small and statistically non-significant effect on ARDEB ( Figure 2).…”
Section: Rodent Anxiety Meta-analyses Page 14mentioning
confidence: 98%
See 3 more Smart Citations
“…Meta-analysis of fifteen articles (Rodgers and Cole, 1993;Haller et al, 2000;Blednov et al, 2001;Cheeta et al, 2001;Lapiz et al, 2001;Wright and Ingenito, 2001;Majercsik et al, 2003;Moragrega et al, 2003;Abramov et al, 2004;Wei et al, 2007;Koike et al, 2009;Santos et al, 2010;Cuenya et al, 2012;Lukkes et al, 2009;Hermes et al, 2011) on social isolation revealed it had a small anxiogenic effect (g = 0.37 [95CI 0.15, 0.58], p = 7.8 x 10 -4 ; Figure 6C). However, Egger's regression revealed funnel plot asymmetry, while trim-and-fill adjustment reduced the anxiogenic effect to only 0.15 g [95CI -0.10, 0.40], a small and statistically non-significant effect on ARDEB ( Figure 2).…”
Section: Rodent Anxiety Meta-analyses Page 14mentioning
confidence: 98%
“…2008; Quintino-dos-Santos et al, 2014; F. M. C. V. Reis et al, 2012;Rodgers and Cole, 1993;Ryu et al, 2009;Santos et al, 2010;Serra et al, 2000;Thorsell et al, 2006;Voikar et al, 2005;Wei et al, 2007;Workman et al, 2011;Wright and Ingenito, 2001;Yildirim et al, 2012;Yorgason et al, 2013;Y. Zhang et al, 2012).…”
Section: Social Isolation Has a Small Effect On Defense Behaviorsmentioning
confidence: 99%
See 2 more Smart Citations
“…While KOR antagonists have been at the forefront of treatment options for psychiatric illnesses, they are also implicated in a medley of other physiological disorders, including salt consumption (Nascimento et al 2012), epilepsy and hypertension (though hypertension is not discussed here, see(Wright & Ingenito 2001, Wright & Ingenito 2003, Wright et al 2000) for further reading). This brings together the importance of the “whole body” perspective when considering KOR drugs as therapeutic treatment for brain-related diseases.…”
Section: Conclusion: Role Of Kors In Stress and Anxiety Potential Asmentioning
confidence: 99%